The Influence of Brand Trust and Product Quality on Repurchase Intention Through Customer Satisfaction among Bluder Cokro Madiun Customers in Jabodetabek - Ratnasari, Riza; Sudarman, Daman (Transpublika Publisher, 2025)
This study aims to analyze the effect of brand trust and product quality on repurchase intention with customer satisfaction as a mediating variable for Bluder Cokro Madiun customers in the Jabodetabek area. The research design uses an explanatory quantitative approach with a survey method of 400 respondents who have bought Bluder Cokro at least twice. The data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 software. The results reveal that brand trust and product quality have a significant effect on customer satisfaction. Furthermore, customer satisfaction and brand trust have a significant influence on repurchase intention. However, a negative relationship was found between product quality and repurchase intention directly, although the mediation of customer satisfaction strengthened the relationship positively. These findings suggest that customer satisfaction plays an important role in bridging brand trust and product quality with customer loyalty. This research provides strategic implications for local culinary MSMEs to increase customer repurchase intention through strengthening product quality and building brand trust.